ANALYSIS OF INFLUENCING FACTORS STREET VENDOR INCOME IN NEW SUB-DISTRICT BAOLAN TOLITOLI REGENCY (Case Study of Arang Tampurung Business) - Ismail, Ismail; Hairuddin, Hairuddin (International Journal of Economic Entrepreneurship and Business Management, 2024)
This study aims to analyze the influence of business capital, working hours, business duration, and education level. The study is a quantitative research with primary data from the results of the questionnaire on a sample of street vendors in the New Village.The number of respondents to street vendors in the new Village is 53.The data from the questionnaire is processed using a linear probability model and processed using SPSS software. The results of the test were obtained on the variable "'business capital has a significant effect on the income of street vendors with  an odd ratio value of 0.27". The variable "working hours have a significant effect on the income of street vendors with  an odd ratio of 0.069".  In this study, the R Square value is 0.180 which means that the influence of the business capital variable (X1) and the variable of working hours (X2) and business length (X3) has an effect on the income variable (Y) by 18% and the remaining 82% is influenced by other independent variables that are not referred to in the variable.Keywords: Business Capital, Working Hours, Length of Business